Online Recruitment of Qualitative Study Participants: Lessons Online Recruitment of Qualitative Study Participants: Lessons Learned - Erika L. Thompson; Stacey B. Griner; Jessica Grace; Grace Maynard; Idara N. Akpan; Kaeli Johnson; Nathaniel Webb; Sarah A. Alkhatib; Nolan S. Kline (New Prairie Press, 2024)
The COVID-19 pandemic contributed to an increase in online recruitment of research participants as in-person interactions were limited. For quantitative and self-administered surveys, fraud and bot detection methods have been initiated to verify intended participants. However, there is limited information on participant authentication during recruitment process for qualitative studies. This study aimed to describe the recruitment and verification process for focus groups and interview participants for two qualitative studies. Participants were recruited through social media, emails, and snowball sampling online. All participants for both studies were screened based on the eligibility criteria. In the first project, 134 respondents met the eligibility criteria. Among those eligible, 46% were suspected to be fraudulent (i.e., fake identity or posed as meeting inclusion criteria when they do not) and up to 39% did not show up for their scheduled focus groups. Suspected participants were identified during screening and identification stage prior to the focus groups. In the second project, 102 respondents met the eligibility criteria for one of the samples; however, 54% of respondents were suspected to be fraudulent. In the second sample, 211 respondents met the eligibility criteria and 88% were suspected to be fraudulent. Additional protocols, such as ReCAPTCHA, ID checks, monitoring recruitment during social media posts, were initiated to further authenticate participants. This paper highlights the challenges of virtual and online recruitment strategies. Findings emphasize the need for researchers to put in place effective and innovative strategies to recruit and authenticate study participants.